The Nasopharynx Swab Test for Coronavirus Disease-2019 Is Mild and Will Not Cause Significant Pain and Anxiety: A Cross-Sectional Study Based on Psychiatrists - Li, Wei; Zhou, Han; Guo, Qian; Li, Guanjun (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Backgroud Laboratory viral nucleic acid testing (NAT), such as nasopharyngeal swab test, is now recommended as the gold standard for the diagnosis of Coronavirus disease-2019(COVID-19). However, the nasopharyngeal swab testing process may cause some discomfort. Objective To investigate the influence of nasopharyngeal swab test on anxiety and pain of psychiatric medical staff. Methods A total of 174 psychiatric medical staff (including 97 doctors, 68 nurses, and 9 administrators ) and 27 controls were included in the current study. A self-designed questionnaire was used to collect their general demographic information (age, gender, marriage, occupation, profession, smoking history, alcohol consumption history, tea drinking history, previous history of anxiety and depression) as well as their subjective experience, such as nausea, vomiting, coughing, worry, fear, etc, during nasopharyngeal swab collection. The Numerical Rating Scale (NRS) and the State-Trait Anxiety Inventory (STAI) were used to assess the subjects' pain and state anxiety, respectively Results There was no statistical differences (p>0.05) in age, marriage, smoker, a history of anxiety and depression, pain scores and anxiety scores between different professions and gender. The results of partial correlation analysis (controlled for gender and history of depression or anxiety) indicated that man was negatively correlated with anxious (r=-0.148, p=0.037) and nervous (r=-0.171 p=0.016), although there was no significant difference in pain and anxiety between men and women. Conclusions 1) there will be mild discomfort during nucleic acid testing, but not enough to cause pain and anxiety; 2. women are more likely to have anxious and nervous during the nucleic acid testing.